2009
DOI: 10.1016/j.bios.2009.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Single cell and neural process experimentation using laterally applied electrical fields between pairs of closely apposed microelectrodes with vertical sidewalls

Abstract: As biomedical research has moved increasingly towards experimentation on single cells and subcellular structures, there has been a need for microscale devices that can perform manipulation and stimulation at a correspondingly small scale. We propose a microelectrode array (MEA) featuring thickened microelectrodes with vertical sidewalls (VSW) to focus electrical fields horizontally on targets positioned in between paired electrodes. These microelectrodes were fabricated using gold electroplating that was molde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…To achieve single-cell resolution, the gaps between adjacent electrodes should be close enough to allow only one cell to be confined between them. By replacing the planar electrodes 54 , 3D vertical sidewall electrodes were used to improve the spatial uniformity of electric treatment on single cells 93, 95, 96 . Using this configuration, single neurons could be transfected with plasmid DNA, and in particular, local delivery of EGTA into a subcellular axon was also demonstrated.…”
Section: The Applications Of Microfluidic Electroporationmentioning
confidence: 99%
“…To achieve single-cell resolution, the gaps between adjacent electrodes should be close enough to allow only one cell to be confined between them. By replacing the planar electrodes 54 , 3D vertical sidewall electrodes were used to improve the spatial uniformity of electric treatment on single cells 93, 95, 96 . Using this configuration, single neurons could be transfected with plasmid DNA, and in particular, local delivery of EGTA into a subcellular axon was also demonstrated.…”
Section: The Applications Of Microfluidic Electroporationmentioning
confidence: 99%
“… 25 , 26 , 27 Closely apposed electrodes (for example, created by ion deposition and photolithography) with sub-millimetre spacing for electroporation of immediately adjacent cells or cell processes within culture chambers have also been investigated. 28 , 29 In such cases, the voltages required to achieve electroporation-based delivery of reporter gene constructs are considerably reduced over conventional electroporation modes (typically less than 10 V in comparison with several 100s V or even 1000 V in conventional electroporation).…”
Section: Introductionmentioning
confidence: 99%
“…Electrical stimulation and directed local electroporation of concrete axons have been achieved by using a MEA in combination with thickened microelectrodes with vertical sidewalls separated by the appropriate distance to host an axon [72]. By combining patch clamp detection of intracellular membrane potential and the application of voltage pulses through the electrodes of a MEA, it could be observed that it is possible to controllably electroporate neurons with the underlying electrodes of the MEA, which could be very useful for transfection purposes.…”
Section: Microelectrode Arrays (Meas)mentioning
confidence: 99%